Multiple Sustainability Dimensions of Retail Sector in Serbia until 2013 - Lovre, Koviljko; Brankov, Tatjana (Industrija, 2016)
In this paper, we have analysed the challenges met by the Serbian retail industry in the transition process, its economic and social significance in Serbian economy and society, as well as its environmental performance. Although liquidity and profitability of this sector is insufficient, positive business gains of the whole retail sector after 2007 seems encouraging. Also encouraging is an increasing number of ISO 9001 and 14001 in the trade which may indicate the ecological commitment of the companies. Generally speaking, our research has shown that the retail market in Serbia is on the path to sustainability development, but further improvements are needed. For that purpose, appropriate institutional solutions must be applied.